Implementation of Corporate Social Responsibility as a Key Factor in Enhancing Innovation and Entrepreneurial Orientation for SME Sustainability: Triple Bottom Line Theory Approach - Hasyim, Abd. Wahab; ., Laela; Mohungo, Yolanda (Journal of Cultural Analysis and Social Change, 2025)
This study aims to investigate the impact of CSR implementation on Entrepreneurial orientation, innovation behavior, and SMEs' sustainability, focusing on the triple bottom line theory approach. This study employs a quantitative approach with SEM-PLS as a tool of analysis. Data were collected by surveying 83 SME owners operating around the PT. NHM mining area in North Maluku, using a structured questionnaire based on validated scales from previous studies. This research adopts a multidimensional approach, measuring CSR across three main dimensions: economic, environmental, and social. The economic dimension assesses CSR’s contribution to competitiveness, efficiency, innovation, and business growth. The ecological dimension examines the role of CSR in driving sustainability-oriented innovation and compliance with environmental regulations. The social dimension evaluates the impact of CSR on employee well-being, community engagement, and institutional and stakeholder pressures. Innovation behavior in this study is measured through three key aspects: idea generation, idea promotion, and idea realization. Meanwhile, entrepreneurial orientation is analyzed based on four dimensions: proactiveness, risk-taking, competitive aggressiveness, and autonomy. SME sustainability is assessed using six key indicators: sales growth, profit growth, asset growth, customer base, and market reach. The analysis shows that CSR significantly enhances SME sustainability (0.529, p = 0.000). However, CSR negatively impacts entrepreneurial orientation (-0.629, p = 0.000) and innovation behavior (-0.300, p = 0.019), indicating potential trade-offs. Entrepreneurial orientation positively influences sustainability (0.373, p = 0.003), while innovation behavior has an insignificant negative effect (-0.236, p = 0.275). The analysis reveals a complex relationship between CSR, indirect effect, entrepreneurial orientation, innovation behavior, and SME sustainability. CSR has a direct positive effect on SME sustainability but negatively impacts it through entrepreneurial orientation (-0.235, p = 0.004), suggesting that CSR may constrain entrepreneurial initiatives. Meanwhile, the indirect effect through innovation behavior is positive but statistically insignificant (0.071, p = 0.360), indicating that CSR-driven innovation does not necessarily enhance sustainability.